2017
DOI: 10.1111/1744-7917.12531
|View full text |Cite
|
Sign up to set email alerts
|

Insect–plant–pathogen interactions as shaped by future climate: effects on biology, distribution, and implications for agriculture

Abstract: Carbon dioxide (CO 2 ) is the main anthropogenic gas which has drastically increased since the industrial revolution, and current concentrations are projected to double by the end of this century. As a consequence, elevated CO 2 is expected to alter the earths' climate, increase global temperatures and change weather patterns. This is likely to have both direct and indirect impacts on plants, insect pests, plant pathogens and their distribution, and is therefore problematic for the security of future food prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 131 publications
(192 reference statements)
0
35
0
Order By: Relevance
“…As a consequence of global warming, the outcomes of plant-insect-microbe interactions are likely to be modified by future climate. Trębicki et al (2017) summarized the current knowledge on the impacts of climate change on plant, insect (both as herbivore or vector) and phytopathogen interactions. Their review brings convicing evidence that plant biochemistry and physiology are altered by increased CO 2 and temperature, with considerable consequences for defence responses against pests and pathogens.…”
Section: Transmission and Spread Of Plant Diseases By Vectoring Insecmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of global warming, the outcomes of plant-insect-microbe interactions are likely to be modified by future climate. Trębicki et al (2017) summarized the current knowledge on the impacts of climate change on plant, insect (both as herbivore or vector) and phytopathogen interactions. Their review brings convicing evidence that plant biochemistry and physiology are altered by increased CO 2 and temperature, with considerable consequences for defence responses against pests and pathogens.…”
Section: Transmission and Spread Of Plant Diseases By Vectoring Insecmentioning
confidence: 99%
“…In general, the strong impacts of endosymbionts on nutritional requirements, digestive and detoxification abilities, stress protection, and ecological niche of their insect hosts (Skidmore & Hansen, 2017;Zhang et al, 2017) have spurred interest in how to manipulate them to increase the success of beneficial insects or reduce the performance of pest insects, another big challenge in the field. Finally, with the rise of the field of microbial mediation of plantinsect interactions, novel directions continuously open up, owing to new insights in the complexity of this type of interactions, and in response to an urgent need to adapt tomorrow's agriculture to food demand and global changes (Trębicki et al, 2017). For instance, recent studies have revealed that many of the microbes that had originally been classified as entomopathogens or insect-associated microbes in fact play important roles in plants during their extensive plant endophytic stage, and vice versa, with important consequences for the plant-microbe-insect interactions.…”
Section: Concluding Remarks and Future Directions For Research On Plamentioning
confidence: 99%
“…CO 2 ‘fertilization’ typically stimulates plant photosynthetic rate, increases plant growth, carbon : nitrogen (C : N) ratio and secondary metabolites in C3 plants (Ainsworth & Long, ; Lindroth, ; Dáder et al ., ; Vassiliadis et al ., ). The assimilation and reassignment of C and N resources in plants under elevated CO 2 (eCO 2 ) can alter the quality of host plants, which in turn influences the performance of herbivorous insects and even tri‐trophic natural enemies (Chen et al ., ; Stiling & Cornelissen, ; Coll & Hughes, ; Sun et al ., ; Trębicki et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Global atmospheric CO 2 concentrations have increased from 280 µL/L before industrialization to 405 µL/L in 2017 (https://www.co2.earth/), and are predicted to reach enemies (Chen et al, 2005a;Stiling & Cornelissen, 2007;Coll & Hughes, 2008;Sun et al, 2011;Trębicki et al, 2017). eCO 2 generally increases the concentrations of phenolics in C3 plants (Peltonen et al, 2005;Matros et al, 2006), and total phenolics and flavonoids in the nitrogenfixation plants under eCO 2 increase much more than the non-nitrogen-fixation plants (Robinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The recent forecast indicated that atmospheric CO 2 concentration will increase to approximately 900 ppm by 2100 (IPCC, 2014). Increasing atmospheric CO 2 concentration alone can be very significant in crop production because of its direct effect on plant physiology and biochemistry (Cornelissen, 2011), and indirect effect on tri-trophic interactions involving plants, herbivores, and predators or pathogens (Robinson et al, 2012; Trębicki et al, 2017). Elevated atmospheric CO 2 also affects the crop production via direct or indirect impact on the physiology and feeding behavior of phytophagous insects (Zvereva & Kozlov, 2006; Massad & Dyer, 2010; O’Neill et al, 2010).…”
Section: Introductionmentioning
confidence: 99%